The Nexus of Biofuels, Climate Change, and Human Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Liquid fuels are a major part of modern life. They supply energy for ground, water, and air transportation as well as power for industrial and farming machinery. But fossil fuels - the dominant liquid fuel in use for well over a century - have many disadvantages. The use of fossil fuels has obvious health downsides, such as emissions of pollutants that are directly harmful to health. The burning of fossil fuels produces greenhouse gases, which contribute to global warming, itself a long-term threat to human health. There have also been health concerns related to insecurity of liquid fuel supplies and the potential of international conflicts being caused by fuel scarcity. Furthermore, there are concerns that the world's large but still limited supply of fossil fuels could be strained by the increasing demand that results from societies around the world achieving greater prosperity. In the face of these concerns, new policies have been created that encourage the development of renewable sources of energy in general and biofuels in particular. In January 2013, the Roundtable on Environmental Health Sciences, Research, and Medicine of the Institute of Medicine held a 2- day, interactive, public workshop on the intersection of biofuels, climate change, and human health. Workshop attendees explored public health issues related to the composition of traditional and alternative fuels and fuel additives, and they discussed the known and potential health impacts associated with the use of these fuels and fuel additives. The Nexus of Biofuels, Climate Change, and Human Health is the summary of that workshop. This report examines air, water, land use, food, and social impacts of biomass feedstock as an energy resource, and the state of the science and health policy implications of using different types (and generations) of biofuels as an energy source.
Keywords: Health and Medicine

Sustainable Development of Algal Biofuels in the United States - National Research Council (The National Academies Press, 2012)
Biofuels made from algae are gaining attention as a domestic source of renewable fuel. However, with current technologies, scaling up production of algal biofuels to meet even 5 percent of U.S. transportation fuel needs could create unsustainable demands for energy, water, and nutrient resources. Continued research and development could yield innovations to address these challenges, but determining if algal biofuel is a viable fuel alternative will involve comparing the environmental, economic and social impacts of algal biofuel production and use to those associated with petroleum-based fuels and other fuel sources. Sustainable Development of Algal Biofuels was produced at the request of the U.S. Department of Energy.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies; Biology and Life Sciences

Water Implications of Biofuels Production in the United States - National Research Council (The National Academies Press, 2008)
National interests in greater energy independence, concurrent with favorable market forces, have driven increased production of corn-based ethanol in the United States and research into the next generation of biofuels. The trend is changing the national agricultural landscape and has raised concerns about potential impacts on the nation's water resources. To help illuminate these issues, the National Research Council held a colloquium on July 12, 2007 in Washington, DC. Water Implications of Biofuels Production in the United States, based in part on discussions at the colloquium, concludes that if projected future increases in use of corn for ethanol production do occur, the increase in harm to water quality could be considerable from the increases in fertilizer use, pesticide use, and soil erosion associated with growing crops such as corn. Water supply problems could also develop, both from the water needed to grow biofuels crops and water used at ethanol processing plants, especially in regions where water supplies are already overdrawn. The production of "cellulosic ethanol," derived from fibrous material such as wheat straw, native grasses, and forest trimmings is expected to have less water quality impact but cannot yet be produced on a commerical scale. To move toward a goal of reducing water impacts of biofuels, a policy bridge will likely be needed to encourage growth of new technologies, best agricultural practies, and the development of traditional and cellulosic crops that require less water and fertilizer and are optimized for fuel production.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Transitioning to Sustainability Through Research and Development on Ecosystem Services and Biofuels: Workshop Summary - National Research Council (The National Academies Press, 2008)
The National Research Council's Roundtable on Science and Technology for Sustainability hosted "Transitioning to Sustainability through Research and Development on Ecosystem Services and Biofuels: The National Academies' First Federal Sustainability Research and Development Forum" on October 17- 18, 2007. The forum discussed sustainability research and development activities related to ecosystem services and biofuels. The objective of the forum was to identify research gaps and opportunities for collaboration among federal agencies to meet the challenges to sustainability posed by the need to maintain critical ecosystem services, to support the development of alternatives to conventional fossil fuels, and to manage oceans and coastal areas. The forum focused primarily on federal activities, but included the participation of representatives from the private sector, universities, and nongovernmental organizations. This book is a summary the discussions from the forum.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies; Earth Sciences

Expanding Biofuel Production and the Transition to Advanced Biofuels: Lessons for Sustainability from the Upper Midwest: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
While energy prices, energy security, and climate change are front and center in the national media, these issues are often framed to the exclusion of the broader issue of sustainability--ensuring that the production and use of biofuels do not compromise the needs of future generations by recognizing the need to protect life-support systems, promote economic growth, and improve societal welfare. Thus, it is important to understand the effects of biofuel production and use on water quality and quantity, soils, wildlife habitat and biodiversity, greenhouse gas emissions, air quality, public health, and the economic viability of rural communities.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Current Methods for Life-Cycle Analyses of Low-Carbon Transportation Fuels in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Transportation is the largest source of greenhouse gas emissions in the United States, with petroleum accounting for 90 percent of transportation fuels. Policymakers encounter a range of questions as they consider low-carbon fuel standards to reduce emissions, including total emissions released from production to use of a fuel or the potential consequences of a policy. Life-cycle assessment is an essential tool for addressing these questions. This report provides researchers and practitioners with a toolkit for applying life-cycle assessment to estimate greenhouse gas emissions, including identification of the best approach to use for a stated policy goal, how to reduce uncertainty and variability through verification and certification, and the core assumptions that can be applied to various fuel types. Policymakers should still use a tailored approach for each fuel type, given that petroleum-based ground, air, and marine transportation fuels necessitate different considerations than alternative fuels including biofuels, hydrogen, and electricity. Ultimately, life-cycle assessments should clearly document what assumptions and methods are used to ensure transparency.
Keywords: Environment and Environmental Studies

Renewable Fuel Standard: Potential Economic and Environmental Effects of U.S. Biofuel Policy - National Research Council (The National Academies Press, 2011)
In the United States, we have come to depend on plentiful and inexpensive energy to support our economy and lifestyles. In recent years, many questions have been raised regarding the sustainability of our current pattern of high consumption of nonrenewable energy and its environmental consequences. Further, because the United States imports about 55 percent of the nation's consumption of crude oil, there are additional concerns about the security of supply. Hence, efforts are being made to find alternatives to our current pathway, including greater energy efficiency and use of energy sources that could lower greenhouse gas (GHG) emissions such as nuclear and renewable sources, including solar, wind, geothermal, and biofuels. The United States has a long history with biofuels and the nation is on a course charted to achieve a substantial increase in biofuels. Renewable Fuel Standard evaluates the economic and environmental consequences of increasing biofuels production as a result of Renewable Fuels Standard, as amended by EISA (RFS2). The report describes biofuels produced in 2010 and those projected to be produced and consumed by 2022, reviews model projections and other estimates of the relative impact on the prices of land, and discusses the potential environmental harm and benefits of biofuels production and the barriers to achieving the RFS2 consumption mandate. Policy makers, investors, leaders in the transportation sector, and others with concerns for the environment, economy, and energy security can rely on the recommendations provided in this report.
Keywords: Environment and Environmental Studies; Energy and Energy Conservation

Airport Environmental Research Roadmap Narrative Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Airports must maintain a safe and efficient facility while considering environmental impacts. Though traditional environmental challenges such as noise and water quality remain, several new themes are emerging, including energy management, sustainability, resiliency, and wildlife management. Airports will need guidelines and practices to help them address these pressing issues, and the first step in the process is to identify knowledge gaps and research needs. The TRB Airport Cooperative Research Program’s ACRP Web-Only Document 45: Airport Environmental Research Roadmap Narrative Report presents a five-year prioritized listing of research needs in the area of airport environmental management. The description of these needs can be used to develop research problem statements for funding consideration. Additional resources included with the report include a research-idea dataset and a Visual Research Roadmap.
Keywords: Transportation and Infrastructure

Bioenergy with Carbon Capture and Storage Approaches for Carbon Dioxide Removal and Reliable Sequestration: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Bioenergy with carbon capture and storage (BECCS) is a technology that integrates biomass conversion to heat, electricity, or liquid or gas fuels with carbon capture and sequestration. BECCS could provide a significant portion of the global energy supply if deployed to its theoretical maximum feasible amount. The future role of BECCS is a subject that divides researchers as estimates of potential future biomass supply vary widely due to differences in approaches used to consider factors such as population development, consumption patterns (e.g., diet), economic and technological development, climate change, and societal priorities concerning conservation versus production objectives. Nevertheless, many integrated assessment models use large-scale deployment of BECCS in scenarios that limit climate change to below 2°C.
Keywords: Environment and Environmental Studies; Earth Sciences

Industrialization of Biology: A Roadmap to Accelerate the Advanced Manufacturing of Chemicals - National Research Council (The National Academies Press, 2015)
The tremendous progress in biology over the last half century - from Watson and Crick's elucidation of the structure of DNA to today's astonishing, rapid progress in the field of synthetic biology - has positioned us for significant innovation in chemical production. New bio-based chemicals, improved public health through improved drugs and diagnostics, and biofuels that reduce our dependency on oil are all results of research and innovation in the biological sciences. In the past decade, we have witnessed major advances made possible by biotechnology in areas such as rapid, low-cost DNA sequencing, metabolic engineering, and high-throughput screening. The manufacturing of chemicals using biological synthesis and engineering could expand even faster. A proactive strategy - implemented through the development of a technical roadmap similar to those that enabled sustained growth in the semiconductor industry and our explorations of space - is needed if we are to realize the widespread benefits of accelerating the industrialization of biology. Industrialization of Biology presents such a roadmap to achieve key technical milestones for chemical manufacturing through biological routes. This report examines the technical, economic, and societal factors that limit the adoption of bioprocessing in the chemical industry today and which, if surmounted, would markedly accelerate the advanced manufacturing of chemicals via industrial biotechnology. Working at the interface of synthetic chemistry, metabolic engineering, molecular biology, and synthetic biology, Industrialization of Biology identifies key technical goals for next-generation chemical manufacturing, then identifies the gaps in knowledge, tools, techniques, and systems required to meet those goals, and targets and timelines for achieving them. This report also considers the skills necessary to accomplish the roadmap goals, and what training opportunities are required to produce the cadre of skilled scientists and engineers needed.
Keywords: Math, Chemistry, and Physics; Biology and Life Sciences; Industry and Labor

Review of the Research Program of the FreedomCAR and Fuel Partnership: Third Report - National Research Council (The National Academies Press, 2010)
The public-private partnership to develop vehicles that require less petroleum-based fuel and emit fewer greenhouse gases should continue to include fuel cells and other hydrogen technologies in its research and development portfolio. The third volume in the FreedomCAR series states that, although the partnership's recent shift of focus toward technologies that could be ready for use in the nearer term--such as advanced combustion engines and plug-in electric vehicles--is warranted, R&D on hydrogen and fuel cells is also needed given the high costs and challenges that many of the technologies must overcome before widespread use.
Keywords: Transportation and Infrastructure; Energy and Energy Conservation

Effects of U.S. Tax Policy on Greenhouse Gas Emissions - National Research Council (The National Academies Press, 2013)
The U.S. Congress charged the National Academies with conducting a review of the Internal Revenue Code to identify the types of and specific tax provisions that have the largest effects on carbon and other greenhouse gas emissions and to estimate the magnitude of those effects. To address such a broad charge, the National Academies appointed a committee composed of experts in tax policy, energy and environmental modeling, economics, environmental law, climate science, and related areas.
Keywords: Industry and Labor; Environment and Environmental Studies

Nutrient Requirements of Swine: Eleventh Revised Edition - National Research Council (The National Academies Press, 2012)
Since 1944, the National Research Council has published 10 editions of the Nutrient Requirements of Swine. This reference has guided nutritionists and other professionals in academia and the swine and feed industries in developing and implementing nutritional and feeding programs for swine. The swine industry has undergone considerable changes since the tenth edition was published in 1998 and some of the requirements and recommendations set forth at that time are no longer relevant or appropriate. The eleventh revised edition of the Nutrient Requirements of Swine builds on the previous editions published by the National Research Council. A great deal of new research has been published during the last 15 years and there is a large amount of new information for many nutrients. In addition to a thorough and current evaluation of the literature on the energy and nutrient requirements of swine in all stages of life, this volume includes information about feed ingredients from the biofuels industry and other new ingredients, requirements for digestible phosphorus and concentrations of it in feed ingredients, a review of the effects of feed additives and feed processing, and strategies to increase nutrient retention and thus reduce fecal and urinary excretions that could contribute to environmental pollution. The tables of feed ingredient composition are significantly updated. Nutrient Requirements of Swine represents a comprehensive review of the most recent information available on swine nutrition and ingredient composition that will allow efficient, profitable, and environmentally conscious swine production.
Keywords: Agriculture

Strategic Issues Facing Transportation, Volume 5: Preparing State Transportation Agencies for an Uncertain Energy Future - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 750: Strategic Issues Facing Transportation, Volume 5: Preparing State Transportation Agencies for an Uncertain Energy Future examines how the mandate, role, funding, and operations of state departments of transportation (DOTs) will likely be affected by changes in energy supply and demand in the next 30 to 50 years.The report also identifies potential strategies and actions that DOTs can employ to plan and prepare for these effects.In addition, the report describes how robust decision-making techniques can be used to help navigate the potential risks and rewards of different policy and management responses under differing surface transportation energy supply-and-demand scenarios.An extended summary of NCHRP Report 750, Volume 5 is available for download. A 4-page brochure and a 2-page brochure that further summarize the research results are also available for download.NCHRP Report 750, Volume 5 is the fifth in a series of reports being produced by NCHRP Project 20-83: Long-Range Strategic Issues Facing the Transportation Industry. Major trends affecting the future of the United States and the world will dramatically reshape transportation priorities and needs. The American Association of State Highway and Transportation Officials (AASHTO) established the NCHRP Project 20-83 research series to examine global and domestic long-range strategic issues and their implications for state departments of transportation (DOTs); AASHTO's aim for the research series is to help prepare the DOTs for the challenges and benefits created by these trends.Other volumes in this series currently available include:• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 1: Scenario Planning for Freight Transportation Infrastructure Investment• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 2: Climate Change, Extreme Weather Events, and the Highway System: Practitioner’s Guide and Research Report• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 3: Expediting Future Technologies for Enhancing Transportation System Performance• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 4: Sustainability as an Organizing Principle for Transportation Agencies• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 6: The Effects of Socio-Demographics on Future Travel Demand
Keywords: Transportation and Infrastructure

Sustainable Infrastructures for Life Science Communication: Workshop Summary - National Research Council (The National Academies Press, 2014)
Advances in the life sciences - from the human genome to biotechnology to personalized medicine and sustainable communities - have profound implications for the well-being of society and the natural world. Improved public understanding of such scientific advances has the potential to benefit both individuals and society through enhanced quality of life and environmental protection, improved K-12 and undergraduate science education, greater understanding of human connections to the natural world, and more sustainable policies and regulations. Yet few systems of support exist to help life scientist communicators share their research with a broad range of public audiences, or engage the public in discussions about their work. Sustainable Infrastructures for Life Science Communication is the summary of a two-part workshop convened in December 2013 and January 2014 by the National Research Council Roundtable on Public Interfaces of the Life Sciences to identify infrastructure-related barriers that inhibit or prohibit life scientists from communicating about their work and characteristics of infrastructure that facilitate or encourage scientists to engage with public audiences. The workshop featured both formal presentations and panel discussions among participants from academia, industry, journalism, the federal government, and nonprofit organizations. The presentations highlighted the motivations of and challenges to life scientist communicators, theoretical approaches to science communication, examples of different types of infrastructure to support science communication, and the need for building more sustainable science communication infrastructures. This report considers communication infrastructure across a range of life science institutions, including federal agencies, academia, industry, and nonprofit organizations and explores novel approaches to facilitate effective science communication.
Keywords: Biology and Life Sciences; Education

A Framework for Assessing Effects of the Food System - Institute of Medicine; National Research Council (The National Academies Press, 2015)
How we produce and consume food has a bigger impact on Americans' well-being than any other human activity. The food industry is the largest sector of our economy; food touches everything from our health to the environment, climate change, economic inequality, and the federal budget. From the earliest developments of agriculture, a major goal has been to attain sufficient foods that provide the energy and the nutrients needed for a healthy, active life. Over time, food production, processing, marketing, and consumption have evolved and become highly complex. The challenges of improving the food system in the 21st century will require systemic approaches that take full account of social, economic, ecological, and evolutionary factors. Policy or business interventions involving a segment of the food system often have consequences beyond the original issue the intervention was meant to address. A Framework for Assessing Effects of the Food System develops an analytical framework for assessing effects associated with the ways in which food is grown, processed, distributed, marketed, retailed, and consumed in the United States. The framework will allow users to recognize effects across the full food system, consider all domains and dimensions of effects, account for systems dynamics and complexities, and choose appropriate methods for analysis. This report provides example applications of the framework based on complex questions that are currently under debate: consumption of a healthy and safe diet, food security, animal welfare, and preserving the environment and its resources. A Framework for Assessing Effects of the Food System describes the U.S. food system and provides a brief history of its evolution into the current system. This report identifies some of the real and potential implications of the current system in terms of its health, environmental, and socioeconomic effects along with a sense for the complexities of the system, potential metrics, and some of the data needs that are required to assess the effects. The overview of the food system and the framework described in this report will be an essential resource for decision makers, researchers, and others to examine the possible impacts of alternative policies or agricultural or food processing practices.
Keywords: Food and Nutrition; Agriculture

Toward Sustainable Agricultural Systems in the 21st Century - National Research Council (The National Academies Press, 2010)
In the last 20 years, there has been a remarkable emergence of innovations and technological advances that are generating promising changes and opportunities for sustainable agriculture, yet at the same time the agricultural sector worldwide faces numerous daunting challenges. Not only is the agricultural sector expected to produce adequate food, fiber, and feed, and contribute to biofuels to meet the needs of a rising global population, it is expected to do so under increasingly scarce natural resources and climate change. Growing awareness of the unintended impacts associated with some agricultural production practices has led to heightened societal expectations for improved environmental, community, labor, and animal welfare standards in agriculture. Toward Sustainable Agricultural Systems in the 21st Century assesses the scientific evidence for the strengths and weaknesses of different production, marketing, and policy approaches for improving and reducing the costs and unintended consequences of agricultural production. It discusses the principles underlying farming systems and practices that could improve the sustainability. It also explores how those lessons learned could be applied to agriculture in different regional and international settings, with an emphasis on sub-Saharan Africa. By focusing on a systems approach to improving the sustainability of U.S. agriculture, this book can have a profound impact on the development and implementation of sustainable farming systems. Toward Sustainable Agricultural Systems in the 21st Century serves as a valuable resource for policy makers, farmers, experts in food production and agribusiness, and federal regulatory agencies.
Keywords: Agriculture; Environment and Environmental Studies

Genetically Engineered Organisms, Wildlife, and Habitat: A Workshop Summary - National Research Council (The National Academies Press, 2008)
Since the first commercial introduction of transgenic corn plants in 1995, biotechnology has provided enormous benefits to agricultural crop production. Research is underway to develop a much broader range of genetically engineered organisms (GEOs), including fish, trees, microbes, and insects, that could have the potential to transform fields such as aquaculture, biofuels production, bioremediation, biocontrol, and even the production of pharmaceuticals . However, biotechnology is not without risk and continues to be an extremely controversial topic. Chief among the concerns is the potential ecological effects of GEOs that interact with wildlife and habitats.
Keywords: Agriculture; Environment and Environmental Studies; Biology and Life Sciences

The National Academies Summit on America's Energy Future: Summary of a Meeting - National Research Council (The National Academies Press, 2008)
There is a growing sense of national urgency about the role of energy in long-term U.S. economic vitality, national security, and climate change. This urgency is the consequence of many factors, including the rising global demand for energy; the need for long-term security of energy supplies, especially oil; growing global concerns about carbon dioxide emissions; and many other factors affected to a great degree by government policies both here and abroad.
Keywords: Energy and Energy Conservation

Hidden Costs of Energy: Unpriced Consequences of Energy Production and Use - National Research Council (The National Academies Press, 2010)
Despite the many benefits of energy, most of which are reflected in energy market prices, the production, distribution, and use of energy causes negative effects. Many of these negative effects are not reflected in energy market prices. When market failures like this occur, there may be a case for government interventions in the form of regulations, taxes, fees, tradable permits, or other instruments that will motivate recognition of these external or hidden costs. The Hidden Costs of Energy defines and evaluates key external costs and benefits that are associated with the production, distribution, and use of energy, but are not reflected in market prices. The damage estimates presented are substantial and reflect damages from air pollution associated with electricity generation, motor vehicle transportation, and heat generation. The book also considers other effects not quantified in dollar amounts, such as damages from climate change, effects of some air pollutants such as mercury, and risks to national security. While not a comprehensive guide to policy, this analysis indicates that major initiatives to further reduce other emissions, improve energy efficiency, or shift to a cleaner electricity generating mix could substantially reduce the damages of external effects. A first step in minimizing the adverse consequences of new energy technologies is to better understand these external effects and damages. The Hidden Costs of Energy will therefore be a vital informational tool for government policy makers, scientists, and economists in even the earliest stages of research and development on energy technologies.
Keywords: Energy and Energy Conservation